The foundation and development of Na Fianna Eireann, 1909 - 16 - HAY, MARNIE (My University, 2008)
This article examines the establishment and development of Na Fianna Eireann, or the Irish National Boy Scouts, in the period 1909?16. It also assesses the contributions of the organisation?s two founders, Countess Constance Markievicz and Bulmer Hobson, in the early years of its existence. Bureau of Military History witness statements, a key source for the history of the Fianna, indicate that a degree of controversy surrounds the relative importance of the pair in the foundation and control of the Fianna movement.
PUBLISHED
Keywords: Na Fianna Eireann; Scouts